Analisis Kemampuan Literasi Sains Siswa Berdasarkan Kerangka PISA pada Pembelajaran IPA - Elsa Marfina Nandiani; Neng Sholihat; Berry Kurnia Vilmala (Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze students' scientific literacy skills based on the Programme for International Student Assessment (PISA) framework for Natural Science (Science) learning. Scientific literacy is an individual's ability to use scientific knowledge, identify questions, and draw conclusions based on evidence to understand and make decisions related to natural phenomena and changes resulting from human activity. This study used a quantitative descriptive method with secondary school students as subjects. Data collection was conducted through a scientific literacy test designed around three core competencies in the PISA framework: explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting scientific data and evidence. The data obtained were analyzed using descriptive statistics to determine the level of students' scientific literacy skills for each indicator. The results showed that students' scientific literacy skills were still in the moderate to low category. The indicator for explaining phenomena scientifically achieved higher achievement than the indicators for evaluating and designing scientific investigations and interpreting scientific data and evidence. These findings demonstrate the need to develop science learning strategies that are more oriented towards improving critical thinking skills, problem-solving, and the application of scientific concepts in everyday life to improve students' scientific literacy in line with the demands of the 21st century.